Increased blastomere number is associated with higher live birth rate in day 3 embryo transfer - Lifeng Tian; Leizhen Xia; Hongbo Liu; Yan Kou; Zhihui Huang; Xingwu Wu; Lu Fan; Jialyu Huang; Qiongfang Wu (BMC, 2022)
Abstract Purpose To study the relationship between blastomere number and pregnancy outcomes of day 3 embryo transfers. Methods This retrospective cohort study included 2237 fresh single day 3 embryo transfer cycles from October 2013 to November 2020. Patients were divided into six groups according to the blastomere number on day 3: ≤ 6-cell (n = 100), 7-cell (n = 207), 8-cell (n = 1522), 9-cell (n = 187), 10-cell (n = 91) and ≥ 11-cell (n = 130). Generalized estimating equation analysis based on multivariate logistic regression model was performed to adjust for potential confounders. Results The live birth rate (LBR) was 19.0%, 27.1%, 38.9%, 32.1%, 44.0% and 53.8% for the ≤ 6-cell, 7-cell, 8-cell, 9-cell, 10-cell and ≥ 11-cell groups, respectively (P < 0.001). Specifically, the ≤ 6-cell group was associated with reduced LBR compared with the 8-cell group (aOR 0.50, 95% CI 0.29-0.86; P = 0.013). Conversely, the odds of live birth were significantly increased in patients transferred with 10-cell embryos (aOR 1.62, 95% CI 1.03-2.53; P = 0.035) and ≥ 11-cell embryos (aOR 2.14, 95% CI 1.47-3.11; P < 0.001) when using the 8-cell embryo group as reference. Similar trends were also observed in the rates of positive hCG test and clinical pregnancy, while no significant differences were detected in miscarriage risk. Conclusion Increased blastomere number was associated with higher LBR in fresh single day 3 embryo transfer cycles. This finding questions the consensus on the reduced developmental potential of fast-cleaving embryos. Further large prospective studies are warranted for confirmation.